Vulnerability of horticulture producers to climate variability and change : the case of Chókwe District, Mozambique - Vilissa, Delfim Julio (African Climate and Development Initiative, 2016)
Climate change is projected to have continued and globally severe environmental, economic and socioeconomic effects. These effects are forecast to be more severe in the agriculture sector, considering that it is one of the most sensitive industries to climate change. Studies from the Mozambican National Institute for Disaster Management (INGC) suggest that Mozambique is among the countries highly vulnerable to climate change due to its geographical location, in the coastal zone. In addition, the majority of its population is entirely dependent on agriculture activities for food and income. For example, in the Chókwe district, tomato production plays a key role in farmers' livelihood; however, this district is prone to weather variability and climate stresses, affecting the region's agricultural performance and making farmers' livelihood even more precarious. There is indeed limited information on this vulnerability, how farmers cope with the risks as well as their need to manage these stresses. The study conducted includes a survey of 43 farmer households in two villages of Chókwe: Massavasse and Muianga. The study then compares farmers' perceived effects of climate variability with actual climate data observed between 1980 and 2012. Meteorological data was analyzed using R software.